Low-temperature wet chemistry synthetic approaches towards ferrites. Issue 18 (8th June 2020) - Diodati, Stefano; Walton, Richard I.; Mascotto, Simone; Gross, Silvia
Abstract : Solution chemistry allows the crystallisation of range of iron oxides, including MFe2 O4 spinels, MFeO3 perovskites and hexaferrites, such as BaFe12 O19, with nanoscale crystallinity and properties suitable for fields such as catalysis and electronics. Abstract : Ferrites are a broad class of iron-containing oxides that includes spinel ferrites MFe2 O4, perovskites MFeO3, and hexagonal ferrites (hexaferrites) such as BaFe12 O19 . These materials have a wide array of applications owing to their diverse properties: notable instances include catalysis, piezoelectric components, magnetic components, biomedical applications, heterogeneous catalysis and photocatalysis. Given the growing importance of environmentally friendly, low-temperature methodologies to obtain functional materials, there is a growing interest in synthetic approaches which are compatible with the principles of "green chemistry". In this context, wet chemistry represents an attractive choice, and furthermore offers the possibility of scale-up for manufacture of materials in volumes for practical application. Though there is a sizeable amount of literature on the synthesis of ferrites, the most common approaches require treatments at temperatures above 200 °C, either as the main synthetic procedure itself (thermal decomposition), or as a post-synthetic step (for example, calcination after sol–gel autocombustion). This review aims at summarising, categorising, classifying and critically discussing the different low-temperature (<200 °C), wet chemistry approaches employed in recent years for the synthesis of ferrites. This will include hydrothermal, solvothermal, sonochemical, and microwave methods, with examples taken from literature making reference to the various sub-classes of ferrites.